Emotional intelligence, quality of life and alexithymia in elders of an institutionalizazed center (European Journal of Health Research, 2017)
At the stage of old age it is important the study of emotions and how these affect to adaptation and quality of life of older people. Some authors show up the importance of emotional intelligence and quality of life. Alexithymia refers to the difficulty to understand and identify feelings and those of others and externally oriented thinking. The aim is study the relationship between emotional intelligence, quality of life and alexithymia in a group of elderly. The participants were 25 elderly in an institutionalized center of Murcia; there were 12 men. The questionnaires were used: The brief inventory of emotional intelligence for major (EQ-I-M20), the questionnaire of qualit evaluation of life in residential context (CECAVIR) and The brief scale of alexitimia of Toronto (TAS-20). It found significant positive correlations between: the difficulty to identify feelings and the social and familiar relations; the difficulty to identify feelings and satisfaction with the life; the difficulty to describe feelings and the social and familiar relations as well as a significant negative correlation between difficulty to describe feelings and adaptability. The results will allow to advance in the implantation of activities that promote the emotional development of the elderly institutionalized persons in favor of his quality of life.
Keywords: Emotional Intelligence; Quality of life; Alexithymia; Elderly